From Looms to Leadership: Women's Empowerment Through Monjulika Chakma's Bain Textile in Bangladesh’s Chittagong Hill Tracts - Sarder Ali Haider; Takrima Jannat (MultiTech Publisher, 2023)
Monjulika Chakma's entrepreneurial foray with Bain Textile in 1965 within Bangladesh's Chittagong Hill Tracts marked more than just a business venture; it underscored the transformative capabilities of social entrepreneurship. Anchored on a vision to champion female weavers of the region, Chakma not only propelled the intricate art of traditional Chakma fabrics to prominence but also paved the way for socio-economic upliftment and cultural preservation. Despite humble beginnings and myriad challenges – from scarce weaving resources to the complexities of marketing in a geographically remote area – Chakma's resilience and adaptability catalyzed Bain Textile's ascent. This paper unravels Bain Textile's trajectory, highlighting its role in preserving Chakma heritage, engendering female empowerment, and fostering community development. Drawing upon Chakma's innovative strategies and collaborative ethos, the study underscores the imperative of tenacity, co-creation, and experimentation within the sphere of social entrepreneurship. Chakma's Bain Textile emerges not just as a business archetype but as a testament to entrepreneurship's potential as a conduit for societal change and cultural reverence